Plasma Rich in Growth Factors (PRGF) Increases the Number of Retinal Müller Glia in Culture but Not the Survival of Retinal Neurons - Ruzafa, Noelia; Pereiro, Xandra; Fonollosa, Alex; Araiz, Javier; Acera, Arantxa; Vecino, Elena (Frontiers in Pharmacology, 2021)
Plasma rich in growth factors (PRGF) is a subtype of platelet-rich plasma (PRP) that stimulates tissue regeneration and may promote neuronal survival. It has been employed in ophthalmology to achieve tissue repair in some retinal pathologies, although how PRGF acts in the retina is still poorly understood. As a part of the central nervous system, the retina has limited capacity for repair capacity following damage, and retinal insult can provoke the death of retinal ganglion cells (RGCs), potentially producing irreversible blindness. RGCs are in close contact with glial cells, such as Müller cells, that help maintain homeostasis in the retina. In this study, the aim was to determine whether PRGF can protect RGCs and whether it increases the number of Müller cells. Therefore, PRGF were tested on primary cell cultures of porcine RGCs and Müller cells, as well as on co-cultures of these two cell types. Moreover, the inflammatory component of PRGF was analyzed and the cytokines in the different PRGFs were quantified. In addition, we set out to determine if blocking the inflammatory components of PRGF alters its effect on the cells in culture. The presence of PRGF compromises RGC survival in pure cultures and in co-culture with Müller cells, but this effect was reversed by heat-inactivation of the PRGF. The detrimental effect of PRGF on RGCs could be in part due to the presence of cytokines and specifically, to the presence of pro-inflammatory cytokines that compromise their survival. However, other factors are likely to be present in the PRGF that have a deleterious effect on the RGCs since the exposure to antibodies against these cytokines were insufficient to protect RGCs. Moreover, PRGF promotes Müller cell survival. In conclusion, PRGF hinders the survival of RGCs in the presence or absence of Müller cells, yet it promotes Müller cell survival that could be the reason of retina healing observed in the in vivo treatments, with some cytokines possibly implicated. Although PRGF could stimulate tissue regeneration, further studies should be performed to evaluate the effect of PRGF on neurons and the implication of its potential inflammatory role in such processes.